Jacobs, Jessica (2010): Sex, tourism and postcolonial encounter: Landscapes of Longing in Egypt - Ortiz Guitart, Anna (Documents d'Anàlisi Geogràfica, 2012)
Jacobs, Jessica (2010) Sex, tourism and postcolonial encounter: Landscapes of Longing in Egypt Farnham: Ashgate, 135 p. ISBN 978 0 7546 4788 1